Revisiting the role of natural gas as a transition fuel - Aguilera, Roberto F.; Aguilera, R. (2019)
© 2019, Springer-Verlag GmbH Germany, part of Springer Nature. The objective of this paper is to assess the potential of natural gas as a transition fuel towards a low- and zero-carbon economy. We use the previously established global energy market model (GEM) to first provide a close match of the historical energy mix and the associated carbon levels. The model is then used to make simulations of how the energy mix and carbon quantities would evolve in the long distant future—the year 2150—if past dynamics were an indication of the future. A similar GEM modeling exercise was carried out in a previous work, using historical data up to the year 2005, showing that natural gas would help slow global carbon growth in the next 50–100 years, thus paving the way towards a low carbon future dominated by non-fossil energy use. The present study uses the most recent statistics, from 2005 to 2017, to verify the accuracy of the original GEM projections. Our findings show continued penetration of natural gas in the energy mix until the mid-twenty-first century and an eventual reduction of carbon levels starting around that time.